2002
DOI: 10.1073/pnas.202336899
|View full text |Cite|
|
Sign up to set email alerts
|

Hitchhiking mapping: A population-based fine-mapping strategy for adaptive mutations inDrosophilamelanogaster

Abstract: lnRV test statistic was incorrect for locus MS3L-11 (last line of Table 2). The conclusion that two regions of significantly reduced variability are located on the X chromosome and the third chromosome remains unchanged. In the right-hand portion of Fig. 1A, the curve shown was also incorrect. The corrected table and figure appear below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
223
0
3

Year Published

2005
2005
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(235 citation statements)
references
References 43 publications
9
223
0
3
Order By: Relevance
“…First, in practice, one obtains P-values for the CLRT by simulating a null distribution under the standard neutral model (Harr et al 2002;Kim and Stephan 2002;Bauer-DuMont and Aquadro 2005;Beisswanger et al 2006;Pool et al 2006), which is problematic when the demographic assumptions of that model are violated ( Jensen et al 2005). Second, the CLRT (and the subsequent GOF) are not applied to randomly chosen loci in practice, but to outlier loci identified by a genome scan (e.g., Harr et al 2002;Bauer-DuMont and Aquadro 2005;Beisswanger et al 2006;Pool et al 2006). Such ascertainment procedures choose loci with very unusual underlying genealogies, resulting in a pattern of spatial variability that may mimic that of a recent selective sweep, such as an excess of highfrequency, derived mutations surrounding a region of reduced diversity (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, in practice, one obtains P-values for the CLRT by simulating a null distribution under the standard neutral model (Harr et al 2002;Kim and Stephan 2002;Bauer-DuMont and Aquadro 2005;Beisswanger et al 2006;Pool et al 2006), which is problematic when the demographic assumptions of that model are violated ( Jensen et al 2005). Second, the CLRT (and the subsequent GOF) are not applied to randomly chosen loci in practice, but to outlier loci identified by a genome scan (e.g., Harr et al 2002;Bauer-DuMont and Aquadro 2005;Beisswanger et al 2006;Pool et al 2006). Such ascertainment procedures choose loci with very unusual underlying genealogies, resulting in a pattern of spatial variability that may mimic that of a recent selective sweep, such as an excess of highfrequency, derived mutations surrounding a region of reduced diversity (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Of particular importance is how such loci are chosen from the tails in the first place. In practice, the choice is not made using the results of the CLRT/GOF (due to computational impracticability), but rather on the basis of a summary of the data (e.g., Harr et al 2002;Glinka et al 2003;Bauer-DuMont and Aquadro 2005;Beisswanger et al 2006;Pool et al 2006). Teshima et al (2006) have recently found that choosing outlier loci on the basis of low levels of diversity is more powerful than choosing on the basis of summaries of the site-frequency spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations